2012
DOI: 10.4103/0974-2727.98679
|View full text |Cite
|
Sign up to set email alerts
|

Florid Erythrophagocytosis on the Peripheral Smear

Abstract: Erythrophagocytosis is a relatively rare observation on blood smears. It has been reported in auto immune hemolytic anemias and sporadically in few other conditions. Here, we report a case of florid erythrophagocytosis with severe anemia following a viral infection in an 18-year-old girl. Her complete blood count (CBC) revealed hemoglobin of 3.6 gm/dl and a hematocrit of 10%. The peripheral smear showed erythrophagocytosis by neutrophils and rosetting of erythrocytes around neutrophils. The direct Coombs test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, there are several case reports of patients with hemolytic conditions such as AIHA in which circulating neutrophils are identified that carry internalized RBCs. [10][11][12][13][14][15][16][17] Nevertheless, this phenomenon has remained unexplained, as it seems highly unlikely that neutrophils capture RBCs in the bloodstream where the shear force is markedly high. Furthermore, it is not known whether neutrophils, under these and other conditions, have a substantial contribution to erythrocyte clearance in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several case reports of patients with hemolytic conditions such as AIHA in which circulating neutrophils are identified that carry internalized RBCs. [10][11][12][13][14][15][16][17] Nevertheless, this phenomenon has remained unexplained, as it seems highly unlikely that neutrophils capture RBCs in the bloodstream where the shear force is markedly high. Furthermore, it is not known whether neutrophils, under these and other conditions, have a substantial contribution to erythrocyte clearance in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrophagocytosis by neutrophils in peripheral smear though an uncommon finding, is a strong predictor towards the diagnosis of PCH (5). Erythrophagocytosis by neutrophils in peripheral smear has been reported rarely AIHA.…”
Section: Discussionmentioning
confidence: 97%
“…Chandrashekhar et al proposed that the presence of erythrophagocytosis in peripheral smear should alert the pathologist for a diagnosis of PCH. (5). Fadeyi EA reported two cases of PCH occurring in children and emphasized the presence of erythrophagocytosis as an important indicator of PCH (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of marked erythrophagocytosis by neutrophils is a relatively rare observation on blood smears, but it is a prominent feature of PCH [3][4][5]. This case highlights the necessity for clinicians to be aware of the importance of erythrophagocytosis in diagnosis of PCH.…”
mentioning
confidence: 99%